Desain Point of Sales untuk Pengelolaan Kantin di Perguruan Tinggi - Kotjoprayudi, Raswyshnoe Boing; Asniar, Asniar; Fithriyah, Silvia Nurul (Yayasan Petra Harapan Bangsa, 2018)
The purpose of this research is to produce a Point of Sales (POS) design that can be applied by the manager of the university canteen. A canteen within a university is a management entity whose engaged in a sales transaction between a selling pedestal tenant, a canteen officer, and a buyer in an university environment. In fact, there are still in several universities that run their business process of managing campus canteen manually. For example, for foods sales transactions they still use a handwritten cash sale note to be submitted to the cashier section and the the payment is recorded. This has an impact on the process of presenting financial statements that are hampered because they require a recapitulation process. In this paper, the case study which is the object of research is the canteen manager in one of the Universities in Bandung. Where in the campus environment, there are at least 85 tenants selling stalls, 6 canteen locations, 8 cashier locations, 30,000 students, and 1,200 employees and lecturers. The canteen finance department is an internal management unit in this case study. Therefore, this study designs the point of sales system using the System Development Life Cycle (SDLC) method with the waterfall model and is designed using object-oriented methods. The design of this study was only carried out until the design process.Tujuan penelitian ini menghasilkan suatu desain Point Of Sales (POS) yang dapat diterapkan oleh pengelola kantin perguruan tinggi. Kantin dalam lingkungan perguruan tinggi dapat merupakan sebuah entitas dalam pengelolaan transaksi penjualan antara penyewa lapak jual, petugas kantin, dan pembeli di lingkungan perguruan tinggi. Pada kenyataanya, masih terdapat beberapa perguruan tinggi yang menjalankan proses bisnis pengelolaan kantin kampus secara manual. Sebagai contoh, untuk transaksi penjualan makanan masih menggunakan nota penjualan tunai yang ditulis tangan untuk diserahkan ke bagian kasir kemudian dicatat pembayarannya. Hal tersebut berdampak pada proses penyajian laporan-laporan keuangan yang terhambat karena membutuhkan proses rekapitulasi. Dalam paper ini, studi kasus yang menjadi objek penelitian adalah bagian pengelola kantin di salah satu perguruan tinggi di Bandung. Dimana dalam lingkungan kampus tersebut, terdapat sekurangnya 85 penyewa lapak jual, 6 lokasi kantin, 8 lokasi kasir, 30.000 mahasiswa, serta 1.200 pegawai dan dosen. Bagian keuangan kantin merupakan unit pengelola internal dalam studi kasus ini. Maka dari itu, penelitian ini merancang system POS menggunakan metode System Development Life Cycle (SDLC) dengan model waterfall serta dirancang menggunakan metode berorientasi objek. Rancangan penelitian ini hanya dilakukan sampai proses desain.